Dietary selenium intake and mortality in two population-based cohort studies of 133 957 Chinese men and women. Issue 16 (20th May 2016) - Sun, Jiang-Wei; Shu, Xiao-Ou; Li, Hong-Lan; Zhang, Wei; Gao, Jing; Zhao, Long-Gang; Zheng, Wei; Xiang, Yong-Bing
Abstract: Objective: To investigate the potential influence of dietary Se intake on mortality among Chinese populations. Design: We prospectively evaluated all-cause, CVD and cancer mortality risks associated with dietary Se intake in participants of the Shanghai Women's Health Study (SWHS) and the Shanghai Men's Health study (SMHS). Dietary Se intake was assessed by validated FFQ during in-person interviews. Cox proportional hazards models were used to calculate hazard ratios (HR) and 95 % CI. Setting: Urban city in China. Subjects: Chinese adults ( n 133 957). Results: During an average follow-up of 13·90 years in the SWHS and 8·37 years in the SMHS, 5749 women and 4217 men died. The mean estimated dietary Se intake was 45·48 μg/d for women and 51·34 μg/d for men, respectively. Dietary Se intake was inversely associated with all-cause mortality and CVD mortality in both women and men, with respective HR for the highest compared with the lowest quintile being 0·79 (95 % CI 0·71, 0·88; P trend <0·0001) and 0·80 (95 % CI 0·66, 0·98; P trend =0·0268) for women, and 0·79 (95 % CI 0·70, 0·89; P trend =0·0001) and 0·66 (95 % CI 0·54, 0·82; P trend =0·0002) for men. No significant associations were observed for cancer mortality in both women and men. Results were similar in subgroup and sensitivity analyses. Conclusions: Dietary Se intake was inversely associated with all-cause and cardiovascular mortality in both sexes, but not cancer mortality.